Status and Prospects of Organic Farming in India - Naik, M. Ramesh; Umesh, H.; Reddy, M. Bhargav; Manta, Munni; Ramanjaneyulu, A. V. (Chronicle of Bioresource Management, 2023)
India is the second largest populous country in the world. The ever increasing population and diminishing land and water resources are mounting pressure for producing more crop from unit area. The technology driven agriculture forced the farmers to use fertilizers and pesticides indiscriminately which inturn led to further degradation of natural resources such as land, water and environment thus depleting human and animal health. Nowadays, sustainability in agriculture is required to conserve resources without jeopardizing the food production system and biodiversity. Organic farming is a form of sustainable agriculture that has received significant regulatory support for its contribution to environmental preservation. These days, organic foods are preferred by consumers because they are produced without synthetic chemicals duly following animal welfare standards. This paper discusses the current status of organic agriculture in food production, certification and various schemes for promoting organic farming.